1999
DOI: 10.1007/pl00007061
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Abscisic Acid in Induction of Androgenesis: A Comparative Study Between Hordeum vulgare L. Cvs. Igri and Digger

Abstract: Under the same mannitol pretreatment and culture conditions, regeneration efficiency in the barley cultivar (cv.) Igri was about 10 times higher than in the cv. Digger, a difference only partially reflected by a difference in viable microspores after anther pretreatment. Therefore, a comparative study between cvs. Igri and Digger was carried out under various pretreatment conditions. For both cultivars, under water, CPW buffer and mannitol pretreatment conditions, there was a positive correlation between micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…In this respect, our data confirm results obtained previously by other authors (Imamura and Harada 1980;Davies and Jones 1991;Van Bergen et al 1999;Wang et al 2000). The ABA effect was much stronger in anthers of 'Mieszko', for which low temperature pretreatment was essential to increase microspores viability and enabled induction of androgenesis.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…In this respect, our data confirm results obtained previously by other authors (Imamura and Harada 1980;Davies and Jones 1991;Van Bergen et al 1999;Wang et al 2000). The ABA effect was much stronger in anthers of 'Mieszko', for which low temperature pretreatment was essential to increase microspores viability and enabled induction of androgenesis.…”
Section: Discussionsupporting
confidence: 95%
“…Davies and Jones (1991) also reported production of ABA in response to treatment with high osmoticum and low temperature. It was also confirmed in studies of Van Bergen et al (1999) in barley anther cultures. Wang et al (2000) suggested that ABA and its signal transduction pathways may be considered as signaling factors involved in the reprogramming of microspore development.…”
Section: Introductionsupporting
confidence: 67%
See 1 more Smart Citation
“…Cold pre-treatment was similarly found to be beneficial for barley (Hordeum vulgare L.), tobacco (Nicotiana tabacum L), or triticale (9Triticose-cale) androgenesis due to improved microspore viability and increased response (Imamura and Harada 1980;van Bergen et al 1999;Wang et al 1999;_ Zur et al 2008). However, pyramiding other stresses such as centrifugation or electroporation on top of the cold stress did not increase ABA levels, indicating no additive effect of the different treatments.…”
Section: Discussionmentioning
confidence: 77%
“…Although little is known in this respect, abscisic acid (Maraschin et al, 2005(Maraschin et al, , 2006Reynolds & Crawford, 1996;Tsuwamoto et al, 2007;van Bergen et al, 1999) and some plant extracellular signal-regulated kinase homologues (Coronado et al, 2002;Seguí-Simarro et al, 2005) have been proposed as intermediate transducers of extracellular stress signals for the activation of specific gene expression programs (reviewed in Seguí-Simarro & Nuez, 2008a). Related to the cellular response to stress, changes in the levels of different heat-shock proteins (HSPs) have been described in several species during stress-induced microspore embryogenesis after exposure to heat, colchicine, or starvation stress (Cordewener et al, 1995;Seguí-Simarro et al, 2003;Smykal, 2000;Zarsky et al, 1995).…”
Section: Microspore/pollen Embryogenesismentioning
confidence: 99%